Increased Intra-Abdominal Pressure as One of the Links in the Pathogenesis of Secondary Diffuse Purulent Peritonitis - D. V. Cherdantsev; O. V. Ovchinnikova; Yu. G. Trofimovich; I. G. Noskov; O. V. Pervova; A. A. Kovalenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to present literature data on the importance of intra-abdominal hypertension in the pathogenesis of peritonitis.   Key points. Secondary purulent peritonitis is a severe and fairly common form of abdominal infection with high mortality. According to statistics, hospitalization of patients with signs of local or diffuse peritonitis is more than 15 % among patients with acute surgical pathologies. One of the factors in the development of complications and an unfavorable prognosis for this disease is increased intra-abdominal pressure. To measure this indicator, a Foley catheter inserted into the bladder is used in medical practice. According to reference values, the optimal level of intra-abdominal pressure does not exceed 5 mmHg. A persistent increase in pressure of 12 mmHg and above indicates the development of intra-abdominal hypertension. An increase in the level of intra-abdominal pressure indicates the progression of the inflammatory destructive process in the abdominal cavity and contributes to the development of multiple organ failure with subsequent fatal outcome with untimely treatment. With an indicator exceeding 20 mmHg, there is a risk of developing abdominal compartment syndrome. This condition is characterized by increased pressure in two or more anatomical areas, which leads to decreased blood flow and subsequent tissue hypoxia. Intra-abdominal hypertension also increases the risk of developing postoperative peritonitis in patients who have undergone laparotomy.   Conclusion. To predict the course of secondary diffuse purulent peritonitis, reduce the risk of complications and mortality, it is necessary to focus on measuring intra-abdominal pressure as a mandatory manipulation in surgical patients. Despite its general availability and ease of implementation, this technique allows assessing the severity of organ dysfunctions.